Optimization of Total Flavonoids Extraction and Α-Glucosidase Inhibitory Activity from Plectranthus amboinicus (Lour.) Spreng. Leaves using the Simplex-Centroid Design - Kunto Wibisono; Syarifah Iis Aisyah; Sri Suhesti; Waras Nurcholis (Molekul, 2019)
The leaves of Plectranthus amboinicus (Lour.) Spreng. (Lamiaceae) is a perennial plant that contained flavonoids compounds with have antidiabetic properties. The aim of the work was to select the best solvent for extraction of the flavonoid compounds from torbangun leaves. A statistical simplex-centroid mixture design for the water, ethanol, and hexane solvents has been used to the extraction of extract yield, flavonoids content, and inhibitory α-glucosidase activity of torbangun leaves.  The ethanol-water extracts showed the highest extract yield with value of 15.92%. The ethanol-hexane extracts presented the highest total flavonoids content, 96.30 mg QE/g, followed by hexane extract (82.91 mg QE/g). The ethanol extract recorded higher inhibitory of α-glucosidase activity, with value of 25.53%, followed by hexane extract (25.21%), and ethanol-water extract (23.02%). The weak correlation between the α-glucosidase inhibition and total flavonoids content showed that flavonoids contribute non-significantly to the α-glucosidase activity.